Educators' perspectives of adopting virtual patient online learning tools to teach clinical reasoning in medical schools: a qualitative study - Kassianos, Angelos P.; Plackett, Ruth; Kambouri, Maria A.; Sheringham, Jessica R. (My University, 2023)
Learning tools using virtual patients can be used to teach clinical reasoning (CR) skills and overcome limitations of using face-to-face methods. However, the adoption of new tools is often challenging. The aim of this study was to explore UK medical educators' perspectives of what influences the adoption of virtual patient learning tools to teach CR.
Keywords: Adoption; Clinical reasoning; Implementation framework; Medical education; Medical students; Online learning; Simulation learning; Virtual patient